Inaugeral Bleasdale Memorial Lecture: Some legal aspects on the development of the fight against doping in sport. - Werner, G. (Proceedings XII FINA World Congress on sports medicine, April 1997 Göteborg, Sweden, 1997)
Zu den Stationen des organisierten Kammpfes gegen Doping im internationalen Schwimmverband FINA. Inhalte sind: - Definition Doping - Dopingkontrolle - Sanktionen - FINA Regeln - Salbutamol